Impact of Educational Intervention on Knowledge and Practice of Universal Precautions among Nurses - Shrestha, Indra (Journal of Patan Academy of Health Sciences, 2015)
Introductions: The purpose of this study was to find out the effectiveness of educational intervention in improving knowledge and practice of universal precautions among nurses. Methods: This was a cross sectional observational study conducted at Patan Hospital in August 2008. Fifty nurses with minimum one year of experience were included. Twelve, out of 50 samples were selected by drawing lot for the study of practice of universal precautions. A semi-structured questionnaire was used to measure the knowledge and practice of universal precautions. Results: The findings revealed that there was significant difference in the pre and post-intervention test mean knowledge. The grand mean score of knowledge and practice of universal precautions as a whole were 31.86 and 44.55 with standard deviations of 10.46 and 3.90; and 68.61 and 87.70 with standard deviations of 3.70 and 2.55 in the pre and post intervention tests respectively. Conclusions: Educational intervention had significant role in increasing knowledge and practice of universal precautions among nurses. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13021 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):57-60